"No More Money, Hannah!": Using HBO's Girls to Teach Force Field Analysis. (September 2021) - Cox, Pamela L.
Research suggests that students today favor a collaborative learning style, short cases, and group activities over semester-long case studies, and they respond well to classroom activities characterized by the use of technology, entertainment, and excitement. Accordingly, this article presents an exercise designed using these types of activities to engage students while teaching them about Lewin's force field analysis, resistance to change, and tactics for overcoming resistance to change. The exercise is designed for late undergraduates or graduate students in a change management course or in a change management module in an organizational behavior course. It provides students an easy, initial exercise to learn and apply force field analysis to a short video scene and a personal experience of change as well as to a more complicated follow-on case study.